OPTIMALISASI PEMBELAJARAN TEKS PIWULANG MELALUI METODE TEAMS GAME TOURNAMENT DAN MEDIA GAME POWERQUIZ UNTUK SISWA KELAS VIII SMP - Vaundra Yudha Perdana; Raheni Suhita; Budi Waluyo (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2018)
This research aims to describe: (1) expediency of Teams Game Tournament method blended with media Game Powerquiz to optimize piwulang text learning; and (2) response assessment from specialist of materials lecturer, specialist of media lecturer and teacher, and reaction from students of class 8th Junior High School about Teams Game Tournament method blended with media Game Powerquiz. The method used is R&D (Research and Development). The datas were collected ares informant and document and then to be analyzed with description qualitative and quantitative for describing expediency of Teams Game Tournament method blended with media Game Powerquiz to optimize piwulang text learning for students of class 8th Junior High School. Result of this research to show that: (1) development process was conducted in some phases covering analysis phase, developer observed the curriculum; design phase, developer designed material and game; development phase, developer made storyboard or draft for development learning media; validate phase, for evaluated material and media; and final phase, to corrected last evaluate; also result of assessment from specialist of materials lecturer 89,7 is very good assessment, result of assessment from specialist of media lecturer 89,5 is very good assessment, result of assessment from teacher 96,6 is very good assessment. Also positive responses from students to proving about Teams Game Tournament method blended with media Game Powerquiz able to be optimize for piwulang text learning.